Analisis Rasio Likuiditas dan Rasio Solvabilitas dalam Menilai Kinerja Keuangan pada PT Akasha Wira International Tbk Periode 2021-2024 - Sarti Enne; Rindiantika; Nia Bonggakarua; Muhammad Haekal Yunus; Rafiqah Asaff (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the financial performance of PT Akasha Wira International Tbk during the 2021–2024 period using a financial ratio analysis approach, specifically focusing on liquidity and solvency ratios. This analysis is essential to assess the company's ability to meet its short-term and long-term obligations and to evaluate the soundness of its capital structure. The liquidity ratios used in this research include the current ratio, quick ratio, and cash ratio. These three ratios provide insight into the company's capacity to settle current liabilities using current assets, either with or without inventories, and with cash or cash equivalents. Meanwhile, to measure solvency, the debt to asset ratio (DAR) and debt to equity ratio (DER) are employed, which illustrate the extent to which the company is financed by debt in comparison to its assets and equity. This study employs a descriptive quantitative method, using secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange (IDX). The data were analyzed to observe the financial performance trends over the four-year period. The results show that the company’s liquidity ratios were consistently above the industry standard, indicating a strong ability to meet short-term obligations. This is a positive indicator for both internal stakeholders and external parties such as investors and creditors. Furthermore, the solvency ratios showed a declining trend year by year, reflecting a healthier capital structure and a reduction in reliance on debt financing. Overall, based on the analysis of liquidity and solvency ratios, it can be concluded that the financial performance of PT Akasha Wira International Tbk from 2021 to 2024 was in a stable and healthy condition. The company demonstrated solid financial management with strong liquidity and a gradual shift towards lower financial risk, offering a positive financial outlook for the future.